Gestão jurídica dos desastres ambientais ocorridos na exploração offshore do petróleo em território nacional - Berwig, Juliane Altmann (Universidade do Vale do Rio dos Sinos, 2014)
Since the Industrial Revolution, the mechanisms of production have become more dynamic, automated, and following these scientific developments increased exploratory development of new models, including the mechanisms for offshore oil as a source of power generation. However, despite the numerous advantages of this new format development, it results in a distribution of systemic risks, which do not distinguishlimits temporal, or generational territorial and linked to several forms of vulnerabilities cause environmental disaster, with alarming consequences too. These disasters that generate damage to the environment, the community, the economy, among other affected sub-systems are unknown and are not absorbed by the law, causing an uncontrolled legal operations in containing the disaster risks. Face of this scenario, this research seeks to understand the actual state of the art, study the instruments that the law can introduce this risk society, capable of managing the risks of environmental disasters. For this purpose, the methodology of the approach, the systemic method will be used, from an observation of legal systems, and political economy, since these are the actors involved in environmental disasters and will also be from the action of these there will be possibility of prevention and precautionary of these. This methodology will allow the performance of the systems is observed, so that the right has been able to selforganize to respond effectively to disaster risks in power generation from offshore oil exploration. In this sense, from a transdisciplinary approach to research, it is understood that for the containment/mitigation, they should be systematized through a process of: investigation, assessment and management of disaster risks. And in the same sense, in the event of a disaster, the law needs to move on to embed in legal action strategies, during and after the occurrence of a disaster, in times of: mitigation, emergency response, compensation and rebuilding. For that, transdisciplinarity arises as a "bridge translation risk" that the sciences "hard" sciences and "soft" are conducted to dialogue and thereby enabled to bring answers to anticipated future events.
Keywords: Gestão jurídica; Desastres; Petróleo; Legal management; Disasters; Oil; ACCNPQ::Ciências Sociais Aplicadas::Direito